2020
DOI: 10.1108/jcm-02-2020-3657
|View full text |Cite
|
Sign up to set email alerts
|

Understanding drivers and outcomes of brand attachment in mobile branded apps

Abstract: Purpose Mobile computing is an emerging trend. Building on motivational theories, brand attachment and mobile application literature, this paper tests a conceptual model with the aim to provide insights into antecedents and outcomes of consumer brand attachment in a mobile app context. Design/methodology/approach A model is developed in which antecedents and outcomes of brand attachment in a branded mobile app context are examined. Data collected from 228 mobile app users were analyzed using PLS-SEM. Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 81 publications
0
16
0
3
Order By: Relevance
“…Within eWOM, researchers have modeled and tested the influence of review, reviewer, product/service and consumer characteristics on consumer outcomes with the goal of better understanding consumer behavior in the e-commerce context, which is dynamic and rapidly evolving [69]. Early eWOM research only considered the influence of positive reviews, although Ho-Dac, et al [70] provided evidence that consumers specifically seek out negative reviews.…”
Section: Research Implicationsmentioning
confidence: 99%
“…Within eWOM, researchers have modeled and tested the influence of review, reviewer, product/service and consumer characteristics on consumer outcomes with the goal of better understanding consumer behavior in the e-commerce context, which is dynamic and rapidly evolving [69]. Early eWOM research only considered the influence of positive reviews, although Ho-Dac, et al [70] provided evidence that consumers specifically seek out negative reviews.…”
Section: Research Implicationsmentioning
confidence: 99%
“…Hedonic motivation is the reason for performing a behavior because of the individual's internal satisfaction (Soni et al, 2019). Hedonic motivation can be measured by indicators such as: Using this brand product gives fun to me; Using this brand product keeps me happy; Using this brand product gives enjoyment to me; Using this brand product stimulates my curiosity (Hong et al, 2017); The entertainment provided by this brand product can satisfy my achievement; The entertainment provided by this brand product is challenging for me; This brand product can symbolize my status; This brand product can continue my positive mood; This brand product can give me a sense of superiority (Yu & Yuan, 2019); Average scores of items of "interpersonal utility"; Average scores of items of "attachment with device"; Average scores of items of "entertainment" (Tran et al, 2020); using this brand is fun; using this brand is enjoyable; using this brand is very entertaining (Nikolopoulou et al, 2021). Numerous studies investigated the direct connection between hedonic motivation and brand attachment.…”
Section: Hedonic Motivationmentioning
confidence: 99%
“…; how likely is it that you will purchase the selected brand online the next time when you need an apparel product? (Chen-Yu et al, 2016); It makes sense to buy this brand instead of any other brand, even if they are the same; Even if another brand has the same features as this brand, I would prefer to buy this brand; If there is another brand as good as this brand, I prefer to buy this brand; If another brand is not different from this brand in any way, it seems smarter to purchase this brand (Tran et al, 2020); I intend to purchase this brand in the future; If I would purchase this product now, I would buy this brand; I intend to purchase this brand when I need this product; Purchasing this brand is my first choice (Kaufmann et al, 2016).…”
Section: Purchase Intentionmentioning
confidence: 99%
“…Consumers' motivations to fulfil their needs also create an attachment to a particular brand. Referring to social identification theory, studies have revealed that consumers' motivations (Hung and Lu 2018;Tran et al 2021), need satisfaction (i.e. autonomy, competence, and relatedness), and need to belong are associated with their brand attachment (Ahn 2019;Hung 2014).…”
Section: Antecedents Of Brand Attachmentmentioning
confidence: 99%